2023
DOI: 10.1007/s12011-022-03542-7
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Toxicity of Oral Administrated Nano-SiO2: Can Food Additives Increase Apoptosis?

Abstract: Nano silicon dioxide (Nano-SiO 2 ) has a great deal of application in food packaging, as antibacterial food additives, and in drug delivery systems but this nanoparticle, despite its wide range of utilizations, can generate destructive effects on organs such as the liver, lung, and kidney. This study aimed to investigate the toxicological effects of nano-SiO 2 through apoptotic factors. For this purpose, 40 female rats in 4 groups (n = 10) received 300, 600, and 900 mg/kg/day of nano-SiO 2 at 20-30 nm size ora… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…The current scientific literature presents several experimental studies on the damaging effect of NPs on the structure and function of the testes and kidneys following exposure through different routes [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 34 ]. Male rodents’ in vitro and in vivo reproductive toxicity caused by different types of inorganic NPs (AgNPs, AuNPs, IONPs, ZnONPs, TiO 2 NPs and NiNPs) was recently evaluated in a systematic review of data published in the last twelve years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The current scientific literature presents several experimental studies on the damaging effect of NPs on the structure and function of the testes and kidneys following exposure through different routes [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 34 ]. Male rodents’ in vitro and in vivo reproductive toxicity caused by different types of inorganic NPs (AgNPs, AuNPs, IONPs, ZnONPs, TiO 2 NPs and NiNPs) was recently evaluated in a systematic review of data published in the last twelve years.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of different NPs depends strongly on their physicochemical characteristics/intrinsic properties [ 34 ]. An oral route for 20 days of NPs of nano-silicon dioxide (nano-SiO 2 ) at a dose of 600 and 900 mg/kg/day was found to induce hyperemia in the kidney [ 21 ]. The study of a silver selenide nanocomposite at a dose of 500 μg/kg revealed swelling of renal convoluted tubules and, as a consequence, the compression of renal glomeruli and the proliferation of connective tissue in the interstitial space of renal tubules, a typical sign of kidney sclerosis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations